2005
DOI: 10.1007/11552055_4
|View full text |Cite
|
Sign up to set email alerts
|

Effective Protection Against Phishing and Web Spoofing

Abstract: Phishing and Web spoofing have proliferated and become a major nuisance on the Internet. The attacks are difficult to protect against, mainly because they target non-cryptographic components, such as the user or the user-browser interface. This means that cryptographic security protocols, such as the SSL/TLS protocol, do not provide a complete solution to tackle the attacks and must be complemented by additional protection mechanisms. In this paper, we summarize, discuss, and evaluate the effectiveness of such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…This thwarts network sniffer attacks. Phishing is prevented by utilizing TLS in bilateral mode and verifying the certificates of both communicating parties [16].…”
Section: Privacy and Securitymentioning
confidence: 99%
“…This thwarts network sniffer attacks. Phishing is prevented by utilizing TLS in bilateral mode and verifying the certificates of both communicating parties [16].…”
Section: Privacy and Securitymentioning
confidence: 99%
“…These overlaps occur due to the use of different terminologies and are also due to the distinct research goals. For example, there have been studies of phishing attacks [14,21,29,7,6]; users' susceptibility to attacks [9,24]; factors exploited to allow an attack to be successful [27,8,12,25] and others. Among this wealth of studies, we found similar findings labelled in different ways.…”
Section: Overviewmentioning
confidence: 99%
“…Unfortunately, this is not the case and it is questionable whether it is possible at all. Note that an MITM can employ many tricks to give the user the impression of being connected to an origin server, for example, using visual spoofing, which is becoming increasingly popular (e.g., [15,16]). In the most extreme case, one may think of an MITM that is able to fully control the GUI of the user's browser.…”
Section: Related Workmentioning
confidence: 99%
“…Before we elaborate on challenge collision attacks, we note that we must make the assumption that the adversary cannot mount a visual spoofing attack (e.g., [15,16]). Otherwise, it is simpler (and hence more likely) that the adversary simply spoofs the challenge to be displayed by the browser to mount an MITM attack.…”
Section: Challenge Collision Attacksmentioning
confidence: 99%